Defects engineering induced room temperature ferromagnetism in transition metal doped MoS2 - Wang, Yiren; Tseng, Li-Ting; Murmu, Peter P.; Bao, Nina; Kennedy, John; Ionesc, Mihail; Ding, Jun; Suzuki, Kiyonori; Li, Sean; Yi, Jiabao (Materials & design, 2017)
First principle calculations are employed to calculate the electronic structure and magnetic properties of transition-metal doped MoS2 considering the effects of defect/defect complex. It shows that pure MoS2 with both Mo and S vacancy are nonmagnetic. Mn, Fe, Co and Ni substitution in Mo site all lead to spin polarized state. Considering defect complex, the results show that (TMMo+TMMo) defect complex has the lowest formation energy at high S pressure and prefers close to each other except for (CoMo+CoMo). Experimentally, we doped Mn, Co, Ni and Fe into MoS2 single crystals. The doping leads to room temperature ferromagnetic ordering and clustering, agreeing well with the first principle calculations. [Display omitted] •First-principles calculations are performed in series of TM doped MoS2 in monolayer and bulk structures;•Both defects and defect complexes are considered using defects engineering;•Formation energies show the preferable sites of dopants and possible ferromagnetism can be obtained in TM doped MoS2;•Experimental results show clear ferromagnetism in TM doped systems, confirming the computational results.